Effects of Vessel Interruption Sequence During Lobectomy for Non-small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Long, Xiang; Wu, Bingxuan; Zhang, Wenxiong; Lv, Guoli; Yu, Dongliang; Peng, Jinhua; Wei, Yiping; Lei, Youming (Frontiers in Surgery, 2021)
Background: For lobectomy in non-small cell lung cancer (NSCLC), whether interrupting the pulmonary vein first (Vein-first) achieves better perioperative and survival outcomes than interrupting the pulmonary artery first (Artery-first) remains controversial. We conducted this meta-analysis to compare outcomes between the two groups to facilitate better surgical decision-making. Methods: Web of Science, EMBASE, Cochrane Library, Ovid MEDLINE, PubMed, ScienceDirect and Scopus were searched for eligible studies comparing Vein-first and Artery-first procedures. The primary endpoints were survival indicators (overall survival [OS], disease-free survival [DFS] and lung cancer-specific survival [LCSS]). Secondary endpoints included intraoperative indicators, hospitalization and follow-up indicators. Results: After screening 2505 studies, 8 studies involving 1714 patients (Vein-First group: 881 patients; Artery-first group: 833 patients) were included. The vein-first group achieved better OS (HR [hazard ratio]: 1.46, 95% confidence interval [CI]: 1.12~1.91, p = 0.005), DFS (HR: 1.60, 95% CI: 1.23~2.08, p < 0.001) and LCSS (HR: 1.64, 95% CI: 1.16~2.31, p = 0.005). The survival rates of OS at 2-5 years, DFS at 1-5 years and LCSS at 3-5 years were also higher in the Vein-First group. Subgroup analyses suggested that the advantages of survival in the Vein-First group were primarily embodied in the subgroups of squamous cell carcinoma (SCC) and earlier pathological TNM stage (I-II). Operative time, intraoperative blood loss, total complications and total recurrences were comparable between the two groups. Conclusions: The Vein-first sequence is the suitable choice of vessel interruption sequence during lobectomy for NSCLC with better survival and similar perioperative outcomes, especially for stage I-II SCC.